Preparation, Thermal Analysis, and Mechanical Properties of Basalt Fiber/Epoxy Composites - Karvanis, Konstantinos; Rusnáková, Soňa; Krejčí, Ondřej; Žaludek, Milan (Polymers, 2020)
In this study, basalt fiber-reinforced polymer (BFRP) composites with epoxy matrix, 20 layers, and volume fraction of fibers Vf = 53.66%, were prepared by a hand lay-up compression molding combined method. The fabric of the basalt fibers is in twill 2/2 weave. Through dynamic mechanical analysis (DMA), their viscoelastic behavior at elevated temperatures and in various frequencies was explored, whereas thermomechanical analysis (TMA) took part in terms of creep recovery and stress-relaxation tests. Moreover, the glass transition temperature (Tg) of the BFRP composites was determined through the peak of the tanδ curves while the decomposition of the BFRP composites and basalt fibers, in air or nitrogen atmosphere, was explored through thermogravimetric analysis (TGA). The mechanical behavior of the BFRP composites was investigated by tensile and three-point bending experiments. The results showed that as the frequency is raised, the BFRP composites can achieve slightly higher Tg while, under the same circumstances, the storage modulus curve obtains a less steep decrease in the middle transition region. Moreover, the hand lay-up compression molding hybrid technique can be characterized as efficient for the preparation of polymer matrix composites with a relatively high Vf of over 50%. Remarkably, through the TGA experiments, the excellent thermal resistance of the basalt fibers, in the temperature range 30-900 °C, was revealed.
Keywords: basalt fiber; TMA; stress-relaxation; glass transition temperature; epoxy composite; DMA; creep recovery